2021
DOI: 10.3390/polym13081274
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Local Self-Healing Ability of Polyurethane Nanocomposites Using Photothermal Polydopamine-Coated Graphene Oxide Triggered by Near-Infrared Laser

Abstract: In this study, we report the self-healing ability of polyurethane (PU) nanocomposites based on the photothermal effect of polydopamine-coated graphene oxide (PDA–rGO). Polydopamine (PDA) was coated on the graphene oxide (GO) surface, while simultaneously reducing GO by the oxidation of dopamine hydrochloride in an alkaline aqueous solution. The PDA–rGO was characterized by Fourier-transform infrared spectroscopy, X-ray diffraction, Raman spectroscopy, thermogravimetric analysis, and scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The chemical bonding of the surface was determined by ATR-FTIR in the range of 650-4000 cm −1 and scan speed (0.2 cm/s). For XPS condition, microfocus X-ray (1486.6 eV) was used with charging correction (adventitious carbon, 284.8 eV) and dual neutralizer (Ar ion + electrons) [31,32]. The pH changes were measured by a pH meter (Mettler Toledo, Columbus, OH, USA) in 5 mL of PBS solution containing Proteinase K at 37 • C for 14 days.…”
Section: Characterization Of Plga Composite Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical bonding of the surface was determined by ATR-FTIR in the range of 650-4000 cm −1 and scan speed (0.2 cm/s). For XPS condition, microfocus X-ray (1486.6 eV) was used with charging correction (adventitious carbon, 284.8 eV) and dual neutralizer (Ar ion + electrons) [31,32]. The pH changes were measured by a pH meter (Mettler Toledo, Columbus, OH, USA) in 5 mL of PBS solution containing Proteinase K at 37 • C for 14 days.…”
Section: Characterization Of Plga Composite Filmsmentioning
confidence: 99%
“…We previously established that PLGA-based biodegradable implants containing magnesium hydroxide (MH) effectively alleviated the adverse effects induced by acidic PLGA byproducts [30,31]. In addition, decellularized extracellular matrix (dECM) is extensively used as a platform for the bioengineering of medical implants to enhance and control the interaction between implants and host tissues [32]. Therefore, PLGA/MH/dECM composite film was fabricated by solvent casting, and then the surface of composite films with fibronectin (FN), polyethylenimine (PEI), and polydopamine (PDA) was coated as described in Section 2.…”
Section: Characterization Of Plga Composite Filmsmentioning
confidence: 99%
“…They can obtain energy from external stimuli, and then convert it into heat to transfer to the TPU matrix and make the temperature of the TPU matrix rapidly increase. It promotes the self-healing process, including wetting, diffusion, recombination, rearrangement, and the formation of an interpenetrating network structure through the interpenetrating bridge at the scratch section [ 38 , 39 , 40 ]. We reported self-healing TPU composites, including reduced GO-water PU [ 41 ], G-TPU [ 42 , 43 ] and GO-TPU [ 44 ], and demonstrated that TPU composites containing appropriated loading of G or GO can achieve a rapid multiple thermal self-healing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works mainly focused on the effect of carbon nanomaterials on TPU self-healing behavior, but did not pay attention to the properties of the TPU matrix [ 37 , 38 , 39 ]. Here, we prepared G-TPU composites with four kinds of TPU masterbathes with different characteristics and investigated the electrical, mechanical, thermal and infrared thermal response and the near-infrared-light-assisted self-healing properties of the composite films prepared by different initial concentrations of TPU and four kinds of TPU masterbathes, respectively, especially discussing the relationship between the characteristics of TPU and the near-infrared thermal response performance and near-infrared-light-assisted self-healing properties of the composite films.…”
Section: Introductionmentioning
confidence: 99%
“…DL/rDL reaction is probably the most well-known chemical reaction used for achieving the self-healing ability in materials [18,19]. Since the first report of thermally reversible polymer networks containing Diels-Alder functionality in 1969 [20], several systems based on this reaction using various functionalities have been investigated and reported [8,21,22].…”
Section: Introductionmentioning
confidence: 99%